HUBUNGAN DERAJAT HIPERTENSI DENGAN PEMANJANGAN WAKTU PULIH SADAR PASIEN PASCA ANESTESI UMUM DI RS PKU MUHAMMADIYAH YOGYAKARTA - Prima Priatma Mamuasa; Ni Ketut Mendri; Budhy Ermawan (Caring : Jurnal Keperawatan, 2018)
Hypertension is included in systemic diseases commonly encountered during physical examination of preanesthesia. Any time prolonged awakening from general anesthesia is one of the most common problems in the recovery room. The main cause is the pharmacological effects of anesthetic drugs, metabolic disorders, and neurological injury. Hypertension becomes one of the most common metabolic disorders in addition to hypoxemia, hypercapnia, hypotension, liver dysfunction, renal failure, endocrine regulatory disorders, and electrolyte imbalances.To know correlation of hypertension degree with prolonged awakening from general anesthesia at IBS RS PKU Muhammadiyah Yogyakarta.This research is a non-experimental quantitative research with analytic observational research type and design used is cross-sectional. The study was conducted on 23 April to 23 May 2018. The study population of this study was all hypertensive patients who performed surgery with general anesthesia at IBS RS PKU Muhammadiyah Yogyakarta within one month. The number of samples is equal to the number of population. Data analysis using chi-square.Respondents with high grade I hypertension did not experience prolonged awakening from general anesthesia (73.1%). In contrast, respondents with high grade II hypertension experienced prolonged awakening from general anesthesia (73.7%) .The results showed a correlation between degree of hypertension and prolonged awakening from general anesthesia (p = 0,002). The odds ratio value obtained 4.8 results so it is known that respondents with degree II hypertension 4.8 times greater risk of experiencing prolonged awakening from general anesthesia than respondents with degree I hypertension.There is a correlation between hypertension degree and prolonged awakening from general anesthesia